LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst and preparation method and application thereof

CN122912928APending Publication Date: 2026-10-16HUNAN CITY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611307236.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

在现有研究中,TiO2对NHCs有较好的降解效果,但TiO2的光谱响应范围比较窄,仅能吸收太阳光中不到5%的波长小于375nm的紫外光,太阳能利用效率非常低

Benefits of technology

本发明通过对TiO2改性使其在可见光波长范围内响应和减少电子空穴复合,并最终提高对太阳光的利用率和光催化量子效率。将LDH/MIL-101(Fe)负载高效可见光响应的TiO2用于典型NHCs去除,然后再对TiO2进行掺杂离子改性。金属离子和非金属离子共掺杂可以实现TiO2在可见光波长范围内响应。Fe3+能捕获TiO2光催化产生光生电子,从而降低光生电-空穴对的复合机率,进一步提升TiO2的光催化效率。稀土元素中镧La原子序数为67,具有最稳定的+3价,生成离子的可能性越大,变价倾向越高,使得其他元素的4f电子容易在4f轨道上发生配布产生电子跃迁。其特殊的电子行为,使得稀土离子La3+的掺杂改变TiO2的光催化性能,提高了TiO2的光催化活性。由此可见,本发明制备的LDH/MIL-101(Fe)/La-Fe-TiO2不仅能解决NHCs从高效吸附到降解的问题,还可在可见光下光响应,实现吸附-光催化降解协同效应,达到高效低能环保效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912928A_ABST
    Figure CN122912928A_ABST
Patent Text Reader

Abstract

The application belongs to the field of photocatalysis, and particularly relates to a LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst, a preparation method thereof and application. A solution containing lanthanum salt and a first iron salt is mixed with a solution containing tetrabutyl titanate, the obtained sol system is sequentially subjected to aging, solidification and calcination, the obtained La-Fe-TiO2 composite photocatalytic material, LDH, a second iron salt, terephthalic acid, a binder and an organic solvent are mixed, and a solvothermal reaction is carried out to obtain the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst. The LDH / MIL-101(Fe) / La-Fe-TiO2 prepared by the application can not only solve the problem of NHCs from efficient adsorption to degradation, but also can be photoresponsive under visible light, realize the synergistic effect of adsorption-photocatalytic degradation, and achieve the effect of efficient, low-energy and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalysis technology, specifically relating to an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst, its preparation method, and its application. Background Technology

[0002] The booming development of the coal chemical industry has inevitably brought about the "three highs" problem: high water consumption, high energy consumption, and high pollution, and its negative impact on sustainable development cannot be ignored. In light of the actual situation of the coal chemical industry, appropriately adjusting the industrial structure, reducing wastewater discharge, and rationally selecting and organically combining treatment processes will be effective ways to alleviate environmental pollution. Currently, the coal chemical industry mainly includes three processes: coal coking, coal liquefaction, and coal gasification. Due to differences in coal type and processes, the composition of pollutants in wastewater varies. The main organic pollutants in the wastewater are phenols, polycyclic aromatic hydrocarbons (PAHs), and nitrogen-containing heterocyclic compounds (NHCs). Studies have shown that NHCs account for approximately 17.5% of the total nitrogen in coking wastewater, especially pyridine, quinoline, and indole, which are typical NHCs in coal chemical wastewater. These organic pollutants have high content, poor biodegradability, and adverse effects such as teratogenicity, carcinogenicity, and mutagenicity. Furthermore, they readily mix with water, ether, alcohol, and benzene in nature, posing a significant threat to plants, animals, and humans once released into the environment. In summary, by systematically elucidating the removal mechanisms of typical NHCs (pyridine, quinoline, and indole), this study has significant research value and application prospects for reducing water pollution and protecting the ecological environment.

[0003] Currently, the main methods for removing NHCs include coagulation and sedimentation, adsorption, and photocatalytic oxidation. Coagulation and sedimentation is widely used in wastewater treatment due to its advantages such as simple and reliable operation, convenient management, economic efficiency, and small footprint. Researchers have effectively solved the difficulties in coagulation and sedimentation of suspended solids in coal gasification wastewater by modifying technologies such as ozone Fenton coagulation, achieving an NHC removal rate of 47.8%; and magnetic coagulation-enhanced wastewater treatment, which improved the NHC removal rate by 25% compared to traditional coagulation. However, coagulation and sedimentation cannot completely remove NHCs from wastewater, making it difficult to meet treatment standards. Adsorption for NHC removal relies on a physicochemical reaction between the adsorbent and NHCs in the wastewater. The development of highly efficient adsorption materials has attracted much attention. Currently, domestic and international research on adsorption materials mainly focuses on the improvement of traditional adsorption materials and the development of "green" adsorption materials. Researchers have prepared adsorbents such as amino-functionalized coking coal, graphene oxide, and aerobic particles to study their adsorption of NHCs. Results show that natural materials like coking coal and waste residues have low adsorption capacity, requiring further improvement. While modified adsorbents such as amino-functionalized coking coal, graphene oxide, and aerobic particles, as well as synthetic adsorbents, have improved NHC adsorption capacity, their high cost and complex processing procedures are significant factors affecting their practical application. Therefore, developing novel adsorbents suitable for NHC removal is of great importance. Magnetic LDH / MIL-101(Fe) core-shell microspheres are a novel enhanced adsorption composite material. Compared to traditional hydrotalcite (LDH), these magnetic LDH / MIL-101(Fe) core-shell microspheres offer stable performance, low cost, high specific surface area and adsorption capacity, easy separation from water, and recyclability, enabling highly efficient removal of pollutants. Meanwhile, the construction of magnetic LDH / MIL-101(Fe) core-shell microspheres not only improves the synthesis methods of LDH and MOFs (MOFs are topological network structures formed by transition metal elements, alkaline earth metal elements, etc., and organic ligands, among which MIL-101(Fe) is the best performing MOF series), but also provides a broad research foundation for the chemical modification, structural design, and performance optimization of adsorbents with excellent comprehensive performance. However, directly using adsorbent materials can only transfer typical NHCs in water from the liquid phase to the solid phase through adsorption, failing to achieve degradation, and their toxic effects will pose a long-term potential risk to the environment. Therefore, it is essential to explore the use of photocatalysts loaded on LDH / MIL-101(Fe) to achieve efficient and harmless treatment of NHCs in water through photocatalytic oxidation technology.

[0004] In NHC degradation research, photocatalytic oxidation technology leverages the strong oxidizing power of photocatalytic oxidants to photocatalytically degrade NHCs into inorganic substances with relatively small molecular weights through the generation of active free radicals, reducing steric hindrance and improving removal efficiency. Nano-TiO2 has become a popular photocatalyst research topic due to its high chemical stability, non-toxicity, and low cost, with its photostability and high efficiency being particularly favored. Existing research shows that TiO2 has a good degradation effect on NHCs, but its spectral response range is relatively narrow, absorbing less than 5% of the ultraviolet light with wavelengths less than 375 nm from sunlight, resulting in very low solar energy utilization efficiency. Furthermore, TiO2 has a low quantum yield of only about 4%, and a high recombination rate of photogenerated carriers. Summary of the Invention

[0005] In view of this, the purpose of this invention is to provide an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst, its preparation method, and its application. The LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst prepared by this invention modifies TiO2 to make it responsive in the visible light wavelength range and reduce electron-hole recombination, thereby ultimately improving the utilization rate of sunlight and the photocatalytic quantum efficiency. By loading La-Fe-TiO2 onto the surface of LDH / MIL-101(Fe), a synergistic effect of adsorption-photocatalytic degradation is achieved, thereby improving the removal rate of nitrogen-containing heterocyclic compounds.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst, comprising the following steps: A solution containing lanthanum salt and first iron salt was mixed with a solution containing tetrabutyl titanate, and the resulting sol system was successively aged, cured and calcined to obtain a La-Fe-TiO2 composite photocatalytic material; The La-Fe-TiO2 composite photocatalyst, LDH, second iron salt, terephthalic acid, binder and organic solvent are mixed and subjected to a solvothermal reaction to obtain the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst.

[0007] Preferably, the calcination temperature is 600~650℃, and the holding time is 2~3h.

[0008] Preferably, the mass ratio of the lanthanum salt to the first iron salt is 0.05~0.07:0.04~0.06.

[0009] Preferably, the mixing of the solution containing lanthanum salt and the first iron salt with the solution containing tetrabutyl titanate is performed by: injecting the solution containing lanthanum salt and the first iron salt into the solution containing tetrabutyl titanate, and continuously stirring mechanically to form a sol system.

[0010] Preferably, the adhesive is polyvinylpyrrolidone.

[0011] Preferably, the temperature of the solvothermal reaction is 110~120℃ and the time is 24~25h.

[0012] Preferably, the second iron salt is ferric chloride.

[0013] The present invention also provides an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst prepared by the preparation method described above, comprising LDH / MIL-101(Fe) microspheres and La-Fe-TiO2 loaded on the surface of the LDH / MIL-101(Fe) microspheres; the LDH / MIL-101(Fe) microspheres have a core-shell structure, with loose microspheres assembled from sheet-like LDH as the shell and MIL-101(Fe) as the core; the La-Fe-TiO2 is TiO2 doped with La and Fe; the La-Fe-TiO2 is uniformly distributed on the surface of the sheet-like LDH.

[0014] This invention also provides the application of the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst described above in the photocatalytic degradation of nitrogen-containing heterocyclic compounds.

[0015] The present invention also provides a method for photocatalytic degradation of nitrogen-containing heterocyclic compounds, comprising the following steps: A photocatalyst is added to water containing nitrogen-containing heterocyclic compounds, and photocatalytic degradation is carried out under visible light irradiation; The photocatalyst is the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst described in the above technical solution.

[0016] This invention provides a method for preparing an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst, comprising the following steps: A solution containing lanthanum salt and first iron salt was mixed with a solution containing tetrabutyl titanate, and the resulting sol system was successively aged, cured and calcined to obtain a La-Fe-TiO2 composite photocatalytic material; The La-Fe-TiO2 composite photocatalyst, LDH, second iron salt, terephthalic acid, binder and organic solvent are mixed and subjected to a solvothermal reaction to obtain the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst.

[0017] Beneficial effects: This invention modifies TiO2 to enable it to respond in the visible light wavelength range and reduces electron-hole recombination, ultimately improving the utilization of sunlight and the photocatalytic quantum efficiency. Highly efficient visible-light-responsive TiO2 loaded with LDH / MIL-101(Fe) is used for the removal of typical NHCs, followed by ion-doping modification. Co-doping with metal and non-metal ions can achieve a visible-light wavelength response in TiO2. Fe 3+ It can capture photogenerated electrons generated by TiO2 photocatalysis, thereby reducing the recombination probability of photogenerated electron-hole pairs and further improving the photocatalytic efficiency of TiO2. Among rare earth elements, lanthanum (La) has an atomic number of 67 and the most stable +3 valence. The greater the possibility of forming ions, the higher the valence change tendency, making it easier for the 4f electrons of other elements to be distributed in the 4f orbital and generate electronic transitions. Its special electronic behavior makes the rare earth ion La... 3+ The doping of TiO2 alters its photocatalytic performance, thereby enhancing its photocatalytic activity. Therefore, the LDH / MIL-101(Fe) / La-Fe-TiO2 prepared in this invention not only solves the problem of efficient adsorption and degradation of NHCs, but also exhibits photoresponsiveness under visible light, achieving a synergistic effect of adsorption-photocatalytic degradation, resulting in high efficiency, low energy, and environmental friendliness. Attached Figure Description

[0018] Figure 1 SEM image of MIL-101(Fe) prepared for Comparative Example 1; Figure 2 Here is a SEM image of the LDH from Example 1; Figure 3 SEM image of LDH / MIL-101(Fe) prepared in Comparative Example 1; Figure 4 SEM image of LDH / MIL-101(Fe) / La-Fe-TiO2 prepared in Example 1; Figure 5 BET characterization diagrams of LDH from Example 1 and LDH / MIL-101(Fe) prepared in Comparative Example 1 are shown. Figure 6 Visible-ultraviolet diffuse reflectance spectra of TiO2, La-Fe-TiO2 and MIL-101(Fe) / La-Fe-TiO2 prepared in Comparative Example 3 and LDH / MIL-101(Fe) / La-Fe-TiO2 (LDH / MOF / La-Fe-TiO2) prepared in Example 1; Figure 7The effect of different pH values ​​on the pyridine removal rates of LDH in Example 1, MIL-101(Fe) prepared in Comparative Example 1, and LDH / MIL-101(Fe) prepared in Comparative Example 1 is shown in the figure. Figure 8 The effect of different dosages on the pyridine removal rate of LDH in Example 1, MIL-101(Fe) prepared in Comparative Example 1, and LDH / MIL-101(Fe) prepared in Comparative Example 1 is shown in the figure. Figure 9 The graph shows the effect of temperature on the photocatalytic degradation of quinoline by LDH / MIL-101(Fe) / La-Fe-TiO2 prepared in Example 1. Figure 10 The image shows a comparison of the photocatalytic degradation results of quinoline by TiO2, La-Fe-TiO2 and MIL-101(Fe) / La-Fe-TiO2 prepared in Comparative Example 3 and LDH / MIL-101(Fe) / La-Fe-TiO2 prepared in Example 1. Detailed Implementation

[0019] This invention provides a method for preparing an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst, comprising the following steps: A solution containing lanthanum salt and first iron salt was mixed with a solution containing tetrabutyl titanate, and the resulting sol system was successively aged, cured and calcined to obtain a La-Fe-TiO2 composite photocatalytic material; The La-Fe-TiO2 composite photocatalyst, LDH, second iron salt, terephthalic acid, binder and organic solvent are mixed and subjected to a solvothermal reaction to obtain the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst.

[0020] Unless otherwise specified, the present invention does not have special requirements on the source of raw materials used, and commercially available products well known to those skilled in the art can be used.

[0021] This invention involves mixing a solution containing lanthanum salt and a first iron salt with a solution containing tetrabutyl titanate, and then subjecting the resulting sol system to aging, curing, and calcination to obtain a La-Fe-TiO2 composite photocatalytic material.

[0022] In one embodiment, the lanthanum salt is lanthanum nitrate, specifically lanthanum nitrate hexahydrate (La(NO3)3·6H2O); the first iron salt is ferric nitrate, specifically ferric nitrate nonahydrate (Fe(NO3)3·9H2O); the solvent in the solution containing the lanthanum salt and the first iron salt includes anhydrous ethanol, ultrapure water, and hydrochloric acid; the volume ratio of the anhydrous ethanol, ultrapure water, and hydrochloric acid is 30~40:3.0~4.0:0.2~0.3, specifically 36:3.0 in this embodiment. :0.2; the concentration of the hydrochloric acid is 2~5 mol / L, and in a specific embodiment it is 3~5 mol / L; the mass ratio of the lanthanum salt to the first iron salt is 0.05~0.07:0.04~0.06, and in a specific embodiment it is 0.0573:0.0534; the mass ratio of the lanthanum salt to the volume of the solvent in the solution containing the lanthanum salt and the first iron salt is (0.05~0.07) g:(33.2~44.3) mL, and in a specific embodiment it is 0.0573 g:39.2 mL.

[0023] As one embodiment, the method for preparing the solution containing lanthanum salt and first iron salt is as follows: anhydrous ethanol, ultrapure water and hydrochloric acid are mixed, lanthanum salt and first iron salt are added, and ultrasonic dispersion is performed to obtain a solution containing lanthanum salt and first iron salt; the ultrasonic dispersion temperature is 15~30℃, specifically 20~25℃ in this embodiment, the power is 150~300W, specifically 200~250W in this embodiment, and the time is 1~2h, specifically 1.5~2h in this embodiment.

[0024] As one embodiment, the preparation method of the tetrabutyl titanate solution is as follows: An organic alcohol is placed in a polytetrafluoroethylene beaker, and tetrabutyl titanate is slowly added dropwise under magnetic stirring, with continuous stirring to form a homogeneous solution; the organic alcohol includes methanol and / or anhydrous ethanol, specifically anhydrous ethanol in this embodiment; the magnetic stirring speed is 400-500 rpm, specifically 450-500 rpm in this embodiment; the dropping rate is 1-2 drops / s, specifically 2 drops / s in this embodiment; the continuous stirring time is 20-30 min, specifically 30 min in this embodiment; the volume ratio of tetrabutyl titanate (TBOT) to the organic alcohol is 9-10:30-40, specifically 9:36 in this embodiment. Methanol has a lower boiling point than ethanol and evaporates too quickly during the sol-gel process, leading to unstable solution concentration, which may affect the homogeneity of the La-Fe-TiO2 precursor.

[0025] In one embodiment, the mixing of the solution containing lanthanum salt and the first iron salt with the solution containing tetrabutyl titanate comprises: injecting the solution containing lanthanum salt and the first iron salt into the solution containing tetrabutyl titanate, and continuously mechanically stirring to form a sol system; the injection rate is 1~2 drops / s, specifically 2 drops / s in this embodiment; the mass ratio of the lanthanum salt to the volume ratio of the tetrabutyl titanate is (0.05~0.07) g:(9~10) mL, specifically 0.0573 g:9 mL in this embodiment; the temperature of the mechanical stirring is 15~30℃, specifically 20~25℃ in this embodiment, the stirring speed is 400~500 rpm, specifically 450~500 rpm in this embodiment, and the duration is 30 min~2 h, specifically 2 h in this embodiment.

[0026] In one implementation, the aging temperature is room temperature, and the time is 12-15 hours, specifically 12 hours in this embodiment; the curing equipment is a forced-air drying oven; the curing temperature is 60-65℃, specifically 65℃ in this embodiment, and the time is 24-25 hours, specifically 24 hours in this embodiment; the calcination temperature is 600-650℃, specifically 600℃ in this embodiment, and the holding time is 2-3 hours, specifically 2 hours in this embodiment; the heating rate to the calcination temperature is 5-6℃ / min, specifically 5℃ / min in this embodiment; the calcination equipment is a muffle furnace; and the calcination is carried out in an air atmosphere.

[0027] As one implementation method, after curing, the process further includes: grinding the cured product to obtain precursor powder; the grinding is carried out to a particle size of 170~200nm, specifically 180~200nm in this embodiment.

[0028] After obtaining the La-Fe-TiO2 composite photocatalyst, the present invention mixes the La-Fe-TiO2 composite photocatalyst, LDH, second iron salt, terephthalic acid, binder and organic solvent, and carries out a solvothermal reaction to obtain LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst.

[0029] As one implementation method, the LDH is prepared as follows: under magnetic stirring, 1.455g of cobalt nitrate hexahydrate, 0.625g of aluminum nitrate nonahydrate, 1.001g of urea, and 0.247g of ammonium fluoride are dissolved in 80mL of deionized water, poured into a 100mL Teflon-lined stainless steel autoclave, heated at 135℃ for 8 hours, the pink precipitate is thoroughly washed with deionized water, and dried at 60℃ overnight to obtain LDH.

[0030] In one embodiment, the adhesive is polyvinylpyrrolidone (PVP); the second iron salt is ferric chloride; the organic solvent is dimethylformamide (DMF); the mass ratio of the La-Fe-TiO2 composite photocatalyst, LDH, the second iron salt, terephthalic acid, and the adhesive is 0.15~0.2:0.1~0.2:0.54~0.6:0.16~0.2:0.3~0.5, and in a specific embodiment, it is 0.15:0.1:0.5406:0.1661:0.3; the mass ratio of the La-Fe-TiO2 composite photocatalyst to the volume ratio of the organic solvent is (0.15~0.2)g:(60~80)mL, and in a specific embodiment, it is 0.15g:60mL.

[0031] In one embodiment, the La-Fe-TiO2 composite photocatalyst material, LDH, second iron salt, terephthalic acid, binder, and organic solvent are mixed under magnetic stirring conditions; the magnetic stirring temperature is 15~30℃, specifically 20~25℃ in this embodiment, the stirring speed is 400~500rpm, specifically 450~500rpm in this embodiment, and the stirring time is 1.5~2h, specifically 2h in this embodiment.

[0032] In one embodiment, the temperature of the solvothermal reaction is 110~120℃, specifically 110℃ in this embodiment, and the time is 24~25h, specifically 24h in this embodiment. After the solvothermal reaction, the process further includes: naturally cooling the product obtained from the solvothermal reaction, separating the solid and liquid, washing the obtained solid, and drying it to obtain the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst. The solid-liquid separation is performed by centrifugation. The washing reagents are dimethylformamide (DMF) and ethanol. The number of washings is 3~5 times, specifically 3~4 times in this embodiment. The drying temperature is 60~65℃, specifically 60℃ in this embodiment, and the time is 2~3h, specifically 2h in this embodiment. The drying is performed by vacuum drying. The vacuum degree of the vacuum drying is -0.08~-0.1MPa, specifically -0.09MPa in this embodiment.

[0033] The present invention also provides an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst prepared by the preparation method described above, comprising LDH / MIL-101(Fe) microspheres and La-Fe-TiO2 loaded on the surface of the LDH / MIL-101(Fe) microspheres; the LDH / MIL-101(Fe) microspheres have a core-shell structure, with loose microspheres assembled from sheet-like LDH as the shell and MIL-101(Fe) as the core; the La-Fe-TiO2 is TiO2 doped with La and Fe; the La-Fe-TiO2 is uniformly distributed on the surface of the sheet-like LDH.

[0034] This invention also provides the application of the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst described above in the photocatalytic degradation of nitrogen-containing heterocyclic compounds.

[0035] The present invention also provides a method for photocatalytic degradation of nitrogen-containing heterocyclic compounds, comprising the following steps: A photocatalyst is added to water containing nitrogen-containing heterocyclic compounds, and photocatalytic degradation is carried out under visible light irradiation; The photocatalyst is the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst described in the above technical solution.

[0036] In one embodiment, the nitrogen-containing heterocyclic compound includes one or more of pyridine, quinoline, and indole, specifically pyridine, quinoline, or indole; the concentration of the nitrogen-containing heterocyclic compound in the water body is 20-100 mg / L, specifically 100 mg / L; the dosage of the photocatalyst in the water body is 0.4-2.4 g / L, specifically 0.4 g / L, 0.8 g / L, 1.2 g / L, 1.6 g / L, 2.0 g / L, or 2.4 g / L; the pH value of the water body containing the nitrogen-containing heterocyclic compound is 2-10, specifically 6, 7, or 8; the intensity of the visible light irradiation is 300-500 W, specifically 400-500 W; and the photocatalytic degradation time is 30-240 min, specifically 60-180 min.

[0037] This invention, by adjusting and optimizing preparation conditions such as calcination temperature, calcination time, pH value of NHC-containing water, binder dosage, and different material proportions, completed adsorption experiments of LDH / MIL-101(Fe) / La-Fe-TiO2 using a solvothermal method. The results show that the adsorption behavior of LDH / MIL-101(Fe) / La-Fe-TiO2 for pyridine conforms to the Freundlich model (R²). 2=0.96) and the pseudo-second-order dynamics model (R 2 =0.99), with a maximum adsorption capacity of 50.1 mg / g. Thermodynamic analysis confirmed that it was a spontaneous (ΔG<0), exothermic (ΔH=-2.04kJ / mol) chemisorption-dominated process. Photocatalytic synergistic experiments showed that under initial pH=7, photocatalyst dosage of 2 g / L, and xenon lamp intensity of 400W, the photocatalyst achieved a degradation rate of 97.3% for 100 mg / L pyridine, which was 17.45% and 30.39% higher than that of single adsorption (84.1%) and photocatalysis (76.8%), respectively. Mechanistic studies indicated that the enrichment effect of LDH / MIL-101(Fe) enriched pyridine molecules on the catalyst surface, and the La / Fe co-doping induced the formation of ·OH and ·O2. - and h + Through synergistic action, it preferentially attacks the CN bond of pyridine, followed by gradual ring-opening and denitrification via intermediates such as N-2-methylamide and malondialdehyde, ultimately mineralizing into CO2, H2O, and NH3-N (GC-MS verification). Free radical quenching experiments further quantified the contribution of active species as h. + (Cavity) > ·OH (hydroxyl radical) > ·O2 - (Superoxide radicals). Cyclic stability testing showed that after five cycles of reuse, the pyridine degradation rate of the composite material remained at 94.5%, and the Zeta potential (-42.3 mV) and BET specific surface area (162.4 m²) remained unchanged. 2 The attenuation rate of less than 5% ( / g) confirms its excellent recyclability. In addition, environmental factor optimization shows that neutral conditions (pH=7), moderate stirring rate (300rpm), and light intensity (400W) are the optimal operating conditions. When the temperature rises to 35°C, the efficiency decreases slightly due to water evaporation.

[0038] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but they should not be construed as limiting the scope of protection of the present invention.

[0039] Example 1 The preparation method of LDH is as follows: Under the action of magnetic stirring, 1.455g of cobalt nitrate hexahydrate, 0.625g of aluminum nitrate nonahydrate, 1.001g of urea and 0.247g of ammonium fluoride are dissolved in 80mL of deionized water, poured into a 100mL stainless steel autoclave lined with Teflon, heated at 135℃ for 8h, the pink precipitate is thoroughly washed with deionized water, and dried at 60℃ overnight to obtain LDH.

[0040] The LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst was prepared by a solvothermal method. 0.0573 g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O, 433.00 g) and 0.0534 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O, 404.00 g) were weighed as doping precursors. 36 mL of anhydrous ethanol was placed in a 250 mL polytetrafluoroethylene beaker, and 9 mL of tetrabutyl titanate (TBOT) was slowly added dropwise at a rate of 2 drops / s under magnetic stirring (500 rpm) for 30 min to form a homogeneous solution A. Separately, 36 mL of anhydrous ethanol was mixed with 3.0 mL of ultrapure water and 0.2 mL of hydrochloric acid (5 mol / L), and the predetermined amount of lanthanum nitrate / ferric salt was added. The mixture was ultrasonically dispersed at 250 W for 2 h at 25℃ to obtain solution B. During dynamic mixing, solution B was injected into solution A at a rate of 2 drops / s, and the mixture was continuously mechanically stirred at 500 rpm for 2 hours at 25°C to form a stable sol system. After aging at room temperature for 12 hours, the sol was cured in a forced-air drying oven at 65°C for 24 hours. The resulting precursor powder (particle size 180~200 nm) was then calcined in a muffle furnace at 600°C for 2 hours with a heating rate of 5°C / min to obtain the La-Fe-TiO2 composite photocatalytic material. After preparation, 0.1 g LDH, 0.15 g La-Fe-TiO2, 0.5406 g ferric chloride hexahydrate (2 mmol), 0.1661 g TPA·terephthalic acid (1 mmol), and 0.3 g PVP polyvinylpyrrolidone were added to 60 mL of the solution. DMF (dimethylformamide) was magnetically stirred at 500 rpm for 1 h at 25 °C, placed in an autoclave, kept at 110 °C for 24 h, and then naturally cooled. The solid was collected by centrifugation, washed three times with DMF and ethanol, and vacuum dried at 60 °C and -0.09 MPa for 2 h to obtain LDH / MIL-101(Fe) / La-Fe-TiO2.

[0041] Example 2 The difference from Example 1 lies in the preparation of La-Fe-TiO2 with different doping amounts: 0.0860 g of lanthanum nitrate hexahydrate (50% more than in Example 1) and 0.0267 g of ferric nitrate nonahydrate (50% less than in Example 1) were weighed out, with the amounts of other precursors remaining unchanged. The above salts were added to solution B (36 mL anhydrous ethanol + 3.0 mL ultrapure water + 0.2 mL hydrochloric acid (1.0 mol / L)) identical to that in Example 1, and ultrasonically dispersed at 25°C and 250 W for 30 min to obtain a clear solution B. Solution A (36 mL anhydrous ethanol + 9 mL tetrabutyl titanate) was mixed with solution B at the same rate (2 drops / second), stirred at 500 rpm for 2 h, aged for 12 h, cured at 65°C for 24 h, ground, and then calcined at 550°C for 2 h with the temperature increased at 8°C / min (both the heating rate and temperature were changed) to obtain La-Fe-TiO2. The same steps were then used to synthesize LDH / MIL-101(Fe) / La-Fe-TiO2, which showed a 30% reduction in pyridine removal rate compared to the composite material synthesized in Example 1.

[0042] Comparative Example 1 Preparation of MIL-101(Fe): 0.1661 g of terephthalic acid and 0.5406 g of ferric chloride hexahydrate were dissolved in 60 mL of N,N-dimethylformamide and stirred at room temperature for 30 minutes until homogeneous. The resulting clear solution was then transferred to a 100 mL high-pressure reactor lined with polytetrafluoroethylene (PTFE) and crystallized at 110 °C for 12 h. After the reaction, the system was allowed to cool naturally to room temperature. The resulting orange precipitate was centrifuged and washed three times each with DMF and anhydrous ethanol to remove unreacted raw materials and solvents. Finally, the product was dried in a forced-air drying oven at 60 °C for 6 h to obtain the MIL-101(Fe) sample.

[0043] Preparation of LDH / MIL-101(Fe): 0.1 g LDH (prepared in Example 1), 0.5406 g ferric chloride hexahydrate (270.302 mmol), 0.1661 g TPA·terephthalic acid (166.131 mmol), and 0.3 g PVP polyvinylpyrrolidone were added to 60 mL of DMF (dimethylformamide) and magnetically stirred for 1 h. The mixture was then placed in an autoclave and kept at 110 °C for 24 h before being allowed to cool naturally. The solid was collected by centrifugation, washed with DMF and ethanol, and dried under vacuum at 60 °C.

[0044] Comparative Example 2 The difference from Example 1 is that the hydrothermal composite temperature of the LDH / MIL-101(Fe) / La-Fe-TiO2 ternary material was changed from 110℃ to 120℃, while all other conditions (including raw material ratio, solvent volume, stirring time, reaction time of 24h, post-treatment, etc.) were exactly the same as in Example 1. The results showed that the removal rate of pyridine decreased by 20%.

[0045] Comparative Example 3 The difference from Example 1 is that 9 mL of tetrabutyl titanate was added dropwise to 36 mL of anhydrous ethanol and magnetically stirred for 30 min, denoted as solution A. 36 mL of anhydrous ethanol was mixed with 3 mL of pure water, and an appropriate amount of hydrochloric acid was added until the pH of the solution reached 2, denoted as solution B. Solution B was added dropwise to solution A while it was being stirred, and stirring continued until a transparent sol was formed. The sol was aged at room temperature for 12 h, and then dried at 65 °C for 24 h. The resulting powder was placed in a muffle furnace and pyrolyzed at 600 °C at a rate of 5 °C / min for 2 h to obtain the TiO2 photocatalyst.

[0046] The difference from Example 1 is that 9 mL of tetrabutyl titanate was added dropwise to 36 mL of anhydrous ethanol, and the mixture was magnetically stirred for 30 min, denoted as solution A. 36 mL of anhydrous ethanol was mixed with 3 mL of pure water, and 0.0573 g of La(NO3)3·6H2O and 0.0534 g of Fe(NO3)3·9H2O were added. An appropriate amount of hydrochloric acid was added until the pH of the solution reached 2, and the mixture was sonicated for 20 min, denoted as solution B. Solution B was added dropwise to the stirring solution A, and stirring continued until a transparent sol was formed. The sol was aged at room temperature for 12 h, and then dried at 65 °C for 24 h. The resulting powder was placed in a muffle furnace and heated to 600 °C at a rate of 5 °C / min, and pyrolyzed for 2 h to obtain a lanthanum-iron-doped TiO2 photocatalyst, denoted as La-Fe-TiO2.

[0047] The difference from Example 1 is that 0.15g La-Fe-TiO2, 0.5406g ferric chloride hexahydrate (2mmol), 0.1661g TPA·terephthalic acid (1mmol), and 0.3g PVP polyvinylpyrrolidone were added to 60mL of DMF (dimethylformamide) and magnetically stirred at 500rpm for 1h at 25℃. The mixture was then placed in an autoclave and kept at 110℃ for 24h before being allowed to cool naturally. The solid was collected by centrifugation, washed three times with DMF and ethanol, and vacuum dried at 60℃ and -0.09MPa for 2h to obtain MIL-101(Fe) / La-Fe-TiO2.

[0048] Performance testing (1) The LDH of Example 1, the MIL-101(Fe) prepared in Comparative Example 1, the LDH / MIL-101(Fe) prepared in Comparative Example 1, and the LDH / MIL-101(Fe) / La-Fe-TiO2 prepared in Example 1 were characterized by SEM. The characterization results showed that the LDH surface structure was a loosely structured sphere, exhibiting a layered structure. Figure 2 La-Fe-TiO2 is uniformly distributed on the LDH / MIL-101(Fe) surface, which exhibits a "core-shell structure." Simultaneously, a small amount of particle agglomeration due to high-temperature calcination can be observed on the surface. Figure 4 From the morphology diagram of LDH / MIL-101(Fe), it can be seen that ( Figure 3 MIL-101(Fe) retains its original spherical structure. Figure 1 The MIL-101(Fe) is uniformly distributed on the LDH nanosheets, indicating that the composite material is well prepared. Furthermore, MIL-101(Fe) is tightly bonded to LDH, increasing the surface roughness and specific surface area of ​​the material.

[0049] (2) Figure 5 BET testing showed that the specific surface area of ​​LDH was 12.204 m². 2 ·g -1 The specific surface area of ​​LDH / MIL-101(Fe) is 146.384 m². 2 ·g -1 After LDH / MIL-101(Fe) was combined, the specific surface area of ​​the composite adsorbent increased from 12.204 m². 2 ·g -1 Increased to 146.384m 2 ·g -1 The composite of LDH / MIL-101(Fe) effectively improved the adsorption performance of the catalyst and enhanced the synergistic effect; as indicated by the visible-ultraviolet diffuse reflectance spectra ( Figure 6 As can be seen, compared with pure TiO2 and La-Fe-TiO2, LDH / MIL-101(Fe) / La-Fe-TiO2 exhibits a significant visible light redshift. The composite catalyst has better visible light absorption capability.

[0050] (3) Experiment to investigate the effect of pH value on adsorption effect A simulated pyridine wastewater solution with an initial concentration of 100 mg / L was placed into three sets of six numbered 100 mL stoppered conical flasks. The pH of the solutions was adjusted to the target values ​​using 0.1 mol / L HCl and NaOH solutions. 0.1 g of each of the three adsorbent materials was weighed using an electronic balance. Three parallel adsorption experiments were conducted under constant temperature (25 ± 0.5 °C) and magnetic stirring at 200 rpm. After 120 min of adsorption, the solution was filtered to obtain a clear liquid. The results are shown in [Figure number missing]. Figure 7 .

[0051] from Figure 7The results show that LDH, MIL-101(Fe), and LDH / MIL-101(Fe) achieved optimal removal rates of pyridine at pH 7, at 78%, 65%, and 84%, respectively. This pH value was selected as the optimal pH for the experiment. Among them, LDH / MIL-101(Fe) exhibited the best adsorption performance. The removal rate of pyridine was lower under acidic and alkaline conditions, while the degradation rate was better around neutral conditions. This is because the catalyst surface's ability to adsorb organic matter, particle aggregation, and surface charge are greatly affected by pH. pH not only affects the electrostatic interactions between the adsorbent surface and the target pyridine, but also, at lower pH values, the weakly basic pyridine undergoes protonation, ultimately acquiring a partial positive charge, which is unfavorable for adsorption on the adsorbent surface. Therefore, a neutral pH is beneficial for pyridine adsorption.

[0052] (4) Adsorption effect experiment of adsorbent dosage The experiment used 50 mL of simulated pyridine-containing wastewater with a pyridine concentration of 100 mg / L. Three adsorbents were weighed out at concentrations of 0.02 g, 0.04 g, 0.06 g, 0.08 g, 0.1 g, and 0.12 g, respectively. The mixture was stirred uniformly at 200 r / min at room temperature for 2 hours until adsorption equilibrium was reached. After stopping stirring, the supernatant was collected, filtered, centrifuged, and the absorbance of the pyridine solution was measured. The experiment was repeated three times. The experimental results are as follows: Figure 8 As shown.

[0053] Depend on Figure 8 The experimental results show that the removal rates of pyridine by the three adsorbents, LDH, MIL-101(Fe) and LDH / MIL-101(Fe), all increase with the increase of adsorbent dosage. The pyridine removal rate reaches its highest when the adsorbent dosage is 0.12g. Among them, the removal rate of pyridine by LDH / MIL-101(Fe) is as high as 90%, which is much higher than that of LDH and MIL-101(Fe). This is because, with the increase of dosage, the contact area between the adsorbent and pyridine increases, and the adsorption sites also increase, thus significantly improving the removal rate of pyridine. However, after exceeding the critical dosage of 0.1g, a plateau effect (Δ removal rate <4%) occurs, the mechanism of which includes dual constraints: (1) the concentration of pyridine in the solution phase drops below the mass transfer threshold, and the adsorption driving force decreases; (2) the site competition effect causes the adsorption efficiency to decay, which is manifested as a decrease in the adsorption capacity per unit mass. This leads to the adsorption capacity increase from the initial 28.6% to 3.2%. At this point, increasing the amount of adsorbent added to increase the number of adsorption sites does not significantly increase the removal rate of pyridine.

[0054] (5) Effect of temperature on the photocatalytic degradation of quinoline by LDH / MIL-101(Fe) / La-Fe-TiO2 prepared in Example 1 The effect of temperature on the photocatalytic degradation of quinoline by LDH / MIL-101(Fe) / La-Fe-TiO2 prepared in Example 1 is as follows: Figure 9 As shown, the degradation rate of quinoline first increases and then decreases with increasing reaction temperature. When the temperature increases from 15℃ to 25℃, the quinoline removal rate increases from 76% to 84%, and the reaction rate constant decreases from 0.02330 min⁻¹. -1 Increased to 0.002870 min -1 This is attributed to the increased collision frequency between quinoline and the active sites of LDH / MIL-101(Fe) / La-Fe-TiO2 at higher temperatures. Simultaneously, higher temperatures favor the migration rate of photogenerated carriers, thereby accelerating the interfacial charge transfer process and promoting the generation of reactive oxygen species. However, when the temperature was further increased to 35℃, the quinoline removal rate decreased by 4.5%, and the reaction rate constant decreased to 0.02473 min. -1 This may be because excessively high temperatures inhibit the spontaneous adsorption process of quinoline on the LDH / MIL-101(Fe) / La-Fe-TiO2 surface, leading to a decrease in the local concentration of the substrate around the active site. Furthermore, high temperatures may accelerate the recombination rate of photogenerated electrons and holes, thus reducing quantum efficiency.

[0055] (6) From Figure 10 As can be seen from the photocatalytic experiment, after 60 min, the degradation rate of quinoline was: LDH / MIL-101(Fe) / La-Fe-TiO2 (87.34%) > MIL-101(Fe) / La-Fe-TiO2 (70.33%) > La-Fe-TiO2 (59.67%) > TiO2 (55.33%), with almost no degradation in the blank group, thus eliminating the interference of quinoline self-photolysis. The LDH / MIL-101(Fe) / La-Fe-TiO2 composite material can organically combine efficient adsorption with photocatalysis. The LDH and MIL-101(Fe) components provide abundant active sites and porous structures, achieving pre-enrichment of quinoline. Under light irradiation, La-Fe-TiO2 generates highly active free radicals, which rapidly mineralize quinoline molecules adsorbed on the surface and in the pores. The coupling effect of adsorption and photocatalysis not only improves the degradation rate but also drives the adsorption equilibrium to further shift by continuously consuming pollutants, forming a virtuous cycle of "adsorption-degradation-re-adsorption".

[0056] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst, characterized in that, Includes the following steps: A solution containing lanthanum salt and first iron salt was mixed with a solution containing tetrabutyl titanate, and the resulting sol system was successively aged, cured and calcined to obtain a La-Fe-TiO2 composite photocatalytic material; The La-Fe-TiO2 composite photocatalyst, LDH, second iron salt, terephthalic acid, binder and organic solvent are mixed and subjected to a solvothermal reaction to obtain the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst.

2. The preparation method according to claim 1, characterized in that, The calcination temperature is 600~650℃, and the holding time is 2~3h.

3. The preparation method according to claim 1, characterized in that, The mass ratio of the lanthanum salt to the first iron salt is 0.05~0.07:0.04~0.

06.

4. The preparation method according to claim 1, characterized in that, The mixing of the solution containing lanthanum salt and the first iron salt with the solution containing tetrabutyl titanate is as follows: the solution containing lanthanum salt and the first iron salt is injected into the solution containing tetrabutyl titanate, and continuous mechanical stirring is performed to form a sol system.

5. The preparation method according to claim 1, characterized in that, The adhesive is polyvinylpyrrolidone.

6. The preparation method according to claim 1, characterized in that, The solvothermal reaction is carried out at a temperature of 110~120℃ for 24~25h.

7. The preparation method according to claim 1, characterized in that, The second iron salt is ferric chloride.

8. The LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that, It includes LDH / MIL-101(Fe) microspheres and La-Fe-TiO2 loaded on the surface of the LDH / MIL-101(Fe) microspheres; the LDH / MIL-101(Fe) microspheres have a core-shell structure, with loose microspheres assembled from lamellar LDH as the shell and MIL-101(Fe) as the core; the La-Fe-TiO2 is TiO2 doped with La and Fe; the La-Fe-TiO2 is uniformly distributed on the surface of the lamellar LDH.

9. The application of the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst according to claim 8 in the photocatalytic degradation of nitrogen-containing heterocyclic compounds.

10. A method for photocatalytic degradation of nitrogen-containing heterocyclic compounds, characterized in that, Includes the following steps: A photocatalyst is added to water containing nitrogen-containing heterocyclic compounds, and photocatalytic degradation is carried out under visible light irradiation; The photocatalyst is the LDH / MIL-101(Fe) / La-Fe-TiO2 composite photocatalyst as described in claim 8.